Temperature effects on moose (Alces alces) activity patterns in Isle Royale National Park - Evavold, Isabella C (ScholarWorks at University of Montana, 2020)
Moose (Alces alces) in Isle Royale National Park impact the ecosystem by browsing tree species and serving as the primary food source for wolves. As a heat-sensitive species, moose are susceptible to the impacts of climate change in the southern extent of their range which includes Isle Royale. Understanding how temperature impacts moose behavior is valuable and can be used to predict how moose may respond to changing temperature in the future. GPS enabled radio-collars with three-axis accelerometers were used to collect one year of temperature and activity data from 6 cow moose in Isle Royale National Park. The data was used to test the relationship between moose activity cycles and temperature using linear regression. Results show that moose activity patterns do change based on temperature. The relationship between temperature and moose behavior can be used to estimate moose browsing impact which determines food availability over time. Understanding the relationship between temperature and moose activity can be used to predict change in moose behavior in response to climate change, which would disrupt the successional progression of vegetation communities and alter the greater Isle Royale ecosystem in the future.